Validation of a Russian version of the Berg Balance Scale - N. A. Suponeva (Nevrologiâ, Nejropsihiatriâ, Psihosomatika, 2021)
Objective: linguistic and cultural adaptation of the original version of Berg Balance Scale (BBS) and assessment its psychometric properties.Patients and methods. The staff of the Validation Center of International Scales and Questionnaires of the Research Center of Neurology received consent from Katherine Berg to validate the BSS in Russia. We carried out the linguocultural ratification during the validation study and prepared a Russian version of the scale. To assess the psychometric properties of the scale (reliability, validity, and sensitivity), we evaluated 55 patients (30 females and 25 males) aged 22–88 years with different neurological disorders (vascular and demyelinating diseases of the central nervous system, peripheral neuropathy, and movement disorders). We analyzed the differences of the total BBS score and the number of patients with high and low risk of falls at the end of rehabilitation compared to baseline to assess the dynamics of changes.Results and discussion. We successfully performed the translation and linguocultural adaptation of the BBS. The scale represents a high level of validity (expert score: 8.6 out of 10 points), reliability (Pearson's correlation coefficient r=0.98, р<0.0001; Cronbach's alpha α=0.94 р<0.001; Cohen's kappa κ=0.71, p<0.0001) and sensitivity (р<0.0001). After a two-week rehabilitation course, the risk of falls significantly decreased (χ2 =4.42; р=0.035); however, the level of independence of movement did not change significantly (F=0.94; р=0.636).Conclusion. The Russian version of the BBS was officially adapted based on the results of the accomplished validation study and is recommended for use both in routine clinical practice and in clinical trials by neurologists and rehabilitologists. The scale is available for downloading by QR code and on the website of Validation Center of International Scales and Questionnaires of the Research Center of Neurology.